2019
DOI: 10.1111/ntwe.12145
|View full text |Cite
|
Sign up to set email alerts
|

Being a woman in an ICT job: an analysis of the gender pay gap and discrimination in Spain

Abstract: Despite policy initiatives aimed at promoting female access to jobs, the information and communication technology (ICT) professions have traditionally been largely monopolised by men. Segregation, gendered stereotypes and environmental factors have a clear impact on educational and professional choices, as well as on working conditions. The spread of ICT to all economic activities has meant that ICT specialists are now to be found everywhere, not only in the ICT sector where many stereotypes related to technic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 32 publications
1
22
0
2
Order By: Relevance
“…Yeo and Grant 2019), defining stereotypes around technology. As a consequence, according to the current results, gender roles and stereotypes turn into steep stairs that women find difficult to climb, limiting women progression in the tourism industry (Segovia-Pérez et al 2019a;Costa et al 2017), and even more in high-tech organizations (Segovia-Pérez et al 2019b).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Yeo and Grant 2019), defining stereotypes around technology. As a consequence, according to the current results, gender roles and stereotypes turn into steep stairs that women find difficult to climb, limiting women progression in the tourism industry (Segovia-Pérez et al 2019a;Costa et al 2017), and even more in high-tech organizations (Segovia-Pérez et al 2019b).…”
Section: Discussionmentioning
confidence: 82%
“…Less women with ICTs degrees impacts on female ICTs sectorial workers, producing an insufficient critical mass that might be promoted. Likewise, the fourth technological revolution have split ICT profession into two profiles, technical or non-technical with hybrid skills (Whitehouse and Diamond 2005) where women tend to gravitate towards 'technically soft' areas where is harder to climb by the leader escalator (Yeo and Grant 2019;Segovia-Pérez et al 2019b;Tabuwe et al 2013;World Economic Forum 2016). Similarly, in the tourism…”
Section: Connections Between Gender Stereotypes Segregation and Ictmentioning
confidence: 99%
“…A second conclusion arises from the improved results obtained in the second year. The program's organizers placed a special emphasis on involving female students from Engineering and applied science degrees, as the literature has shown that this group has even worse possibilities of gaining managerial positions in ICT sectors and occupations [56]. The survey data from 2018, in which there were more students from engineering degrees, confirmed that there was a lower score for the item related to their previous knowledge of the subjects than in 2017.…”
Section: Discussionmentioning
confidence: 99%
“…A second conclusion arises from the increased results obtained on the second year. The program's organizers had placed a special emphasis on involving female students from Engineering or applied science degrees, as the literature has shown that this group has even worse possibilities for gaining managerial positions in ICT sectors or occupations [45]. In the survey data from 2018, in which there were more students from engineer degrees, confirmed that there was a low score on the Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 5 September 2019 doi:10.20944/preprints201909.0051.v1…”
Section: Discussionmentioning
confidence: 99%